FAKTOR – FAKTOR YANG MEMPENGARUHI TINGKAT PENERAPAN TEKNOLOGI PADA KELOMPOK TANI SRI MAKMUR DALAM BUDIDAYA PADI ORGANIK DI DESA SUKOREJO KECAMATAN SAMBIREJO KEBUPATAN SRAGEN - Murni Shinta Dewi (FP AGRI 16 UMY 026, 2016)
The aims of this research are to find information about Sri Makmur member’s profile, the level of application technology in cultivate organic rice, and factors which influence the level of application technology in organic rice cultivation. Respondents in this research are decided by random sampling method. Data is analyzed by table description. The result of this research shows that level of application technology in organic rice cultivation is in high category because farmers have been applying the cultivation based on INOFICE standard. Informal education, time of farming, and level of cosmopolitan are not influence the level of application technology in organic rice cultivation.